Aesthetically improved and efficient tannin–metal chelates for the treatment of dentinal hypersensitivity. Issue 1 (22nd December 2016) - Ju, Sung-Won; Prajatelistia, Ekavianty; Jun, Sang Ho; Hwang, Dong Soo; Ahn, Jin-Soo; Sanandiya, Naresh D.
Abstract : Tannin–metal chelates for the efficient nucleation of hydroxyapatite and an aesthetically improved solution for the dentinal hypersensitivity treatment. Abstract : Dentinal hypersensitivity is an acute transient pain caused by the exposition of the dentinal tubules. The exposed tubules not only cause hypersensitivity but also cause the yellow coloration of the teeth due to their dominance in teeth coloration. An occlusion of the open dentinal tubules by the in situ biomineralization of hydroxyapatite (HAp) is so far the most effective method to alleviate the dentinal hypersensitivity. In recent years, several remineralization strategies, employing various substrates, have been studied for the treatment of dentinal hypersensitivity. However, aesthetically ideal solutions that include the tooth whitening aspect are poorly studied alongside with the tubular occlusion. Herein, the aesthetical improvement along with significant bioremineralization of the HAp crystals for the treatment of dentinal hypersensitivity was examined after a tannin (TA)–metal (ions and oxides) chelates mediated mineralization. Thus, demineralized human molar disks were treated with tannin-based chelates (TA–M). Briefly, TA–M denotes TA combined with 5 different daily intake metal ions and metal oxides, such as Sr(NO3 )2, Fe2 O3, TiO2, CaCl2, VCl3, and a non-metal oxide SiO2 in separate experiments. The samples were coated in the TA–M solution for 4 min followed by immersion in an artificial saliva for 7 days. Biomineralized HAp crystals were well-characterized by various analytical techniques. Among these, TA–Sr(NO3 )2 and TA–TiO2 exhibited the most promising results, as they occluded ca. 79% and 68% of the dentinal tubules, respectively, with brighter color changes after the treatment. This desensitizing solution camouflaged the exposed dentin by its whitening effect using biocompatible Sr and Ti oxides, which may be potential for developing facile 'at-home' aesthetically effective dental desensitizer solution.